The Risk Factors occurrence of contact dermatitis: a cross sectional study - Cynthia ayuningtias; Eko Krisnarto; Kanti Ratnaningrum (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2016)
Abstract.Contact dermatitis is a disease that is most often found in the majority of cases dermatology. Several factors can be act as cause of contact dermatitis, therefore the researchers wanted to know the risk factors that contribute to the incidence of contact dermatitis.This work is an analytic observational studies conducted in RSUD Tugurejo hospitals of Semarang with cross sectional approach using total sampling method. In this work, primary data were taken from direct interviews and secondary data were derived from medical records. Data analysis using chi square test. Analysis of the 65 samples showed that there are a relationship between age (p = 0.004), gender (p = 0.002), history of atopic (p = 0.004), irritants (p = 0.000), duration of contact (p = 0.000), and the location lesions (p = 0.000) on the incidence of contact dermatitis. It can be concluded that there is a relationship between age, sex, history of atopic, irritants, contact time and location of the lesions on the incidence of contact dermatitis in Tugurejo hospitals of Semarang.